Transient field-resolved reflectometry at 50-100 THz - Neuhaus, Marcel; Schoetz, Johannes; Aulich, Mario; Srivastava, Anchit; Kimbaras, Dziugas; Smejkal, Valerie; Pervak, Vladimir; Alharbi, Meshaal; Azzeer, Abdallah M.; Libisch, Florian; Lemell, Christoph; Burgdoerfer, Joachim; et al. (Optica, 2022)
Transient field-resolved spectroscopy enables studies of ultrafast dynamics in molecules, nanostructures, or solids with sub-cycle resolution, but previous work has so far concentrated on extracting the dielectric response at frequencies below 50 THz.Here,we implemented transient field-resolved reflectometry at 50-100THz(3-6μm) withMHzrepetition rate employing 800 nm few-cycle excitation pulses that provide sub-10 fs temporal resolution. The capabilities of the technique are demonstrated in studies of ultrafast photorefractive changes in semiconductors Ge and GaAs, where the high frequency range permits to explore the resonance-freeDrude response. The extended frequency range in transient fieldresolved spectroscopy can further enable studies with so far inaccessible transitions, including intramolecular vibrations in a large range of systems.
CRIS-Team Scopus Importer:2023-04-20